Notes on The Current Distribution and Abundance of The Frog Genus Leptophryne spp. (Anura: Bufonidae) in Gede Pangrango National Park - Noer, Mohamad Isnin; Intani, Ratih Tryas; Prasetya, Priya Yuga; Lestari, Alvita Dwi; Darmawan, Boby (Universitas Gadjah Mada, 2023)
We reported the current distribution of Leptophryne spp. in Gede Pangrango National Park. Leptophryne cruentata was recorded in Cibodas (Cikundul waterfall and Goa Lalay), Selabintana (Cibeureum Waterfall), and Goalpara (Rasta Waterfall), whereas Leptophryne borbonica was only reported from a creek at lowland forest of Bodogol. Goa Lalay and Rasta waterfall were explicitly reported as new distribution locations of Leptophryne cruentata. It was strictly found at a higher elevation usually within reach of waterfalls that generate substantial background noise, except in Cibodas in which Leptophryne cruentata can also be found in two noisy creeks located at a fairly great distance from waterfalls (100 – 170 meters).